Teachers’ Experience in EFL Class by Implementing Blended Learning During Covid-19: Narrative Inquiry - Arisandi Setiyawan; Lucky Rizkiyanto (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study presents the story of experience of EFL teacher in teaching and learning process during pandemic by implementing blended learning. The research design was qualitatively through narrative inquiry. Meanwhile, the reach instrument used by the teacher was narrative box and interview guide. Next, the researcher analyzed the story by re-telling narratively, the researcher then segmented the narrative data into themes. The finding of this study reveals that the teacher tried to apply suitable online platform to teach in blended learning, then it was decided that the teacher used Google classroom and WhatsApp. This application was chosen because of the school policy and it was easier for the students to be implemented. Moreover, there were some problems in its implementation; those were internet connection, and students’ awareness.